Preparation and degradation characteristics of biodegradable elastic poly (1, 3-trimethylene carbonate) network. (November 2021) - Liu, Xiliang; Liu, Song; Li, Kaiqi; Feng, Shaomin; Fan, Youkun; Peng, Lijun; Wang, Xin; Chen, Dongliang; Xiong, Chengdong; Bai, Wei; Zhang, Lifang
Highlights: PTMC networks are prepared with TMPTA, PETA, PET4A by γ irradiation under vacuum. The cross-linking reaction increases PTMC's tensile strength and shape stability. Porcine pancreatic lipase accelerates the degradation of the PTMC network. Due to interfacial activation, the PTMC network's surface arises holes and cracks. PTMC network is biocompatible and nontoxic. Abstract: As soft-tissue materials, poly (1, 3-trimethylene carbonate) (PTMC) must have adequate mechanical properties as well as good shape stability under long-term cyclic deformation conditions. With trimethylolpropane triacrylate (TMPTA), pentaerythritol triacrylate (PETA), and pentaerythritol tetraacrylate (PET4A) as crosslinking agents, PTMC networks were prepared by gamma irradiation under vacuum to improve mechanical properties and resist creep. FTIR demonstrated that PTMC networks were successfully prepared. The PTMC network containing PETA had the highest tensile strength due to physical crosslinking and chemical crosslinking. The tensile strength of the PTMC networks decreased as the irradiation dose increased. Porcine pancreatic lipase (PPL) was a glycoprotein made up of amino acids, mannose, and N -acetyl-glucose units. The effect of PPL on the degradation characteristics of PTMC and PTMC network was evaluated. PTMC warped and curled up during degradation, while the PTMC network maintained its initial shape. PPL effectively accelerated the degradation of the PTMC network. The surface of the PTMC network developed holes and cracks due to interfacial activation. The network's formation restricted chain segment migration. In the early stage of degradation, the PTMC network was degraded slowly. However, the mass loss of the PTMC network exceeded that of the PTMC after 4 weeks, which was attributed to the formation of surface defects. Cell tests revealed that the PTMC network was biocompatible and nontoxic. Therefore, biodegradable elastic PTMC networks with adequate mechanical strength and shape stability are expected to be used in soft tissue implantation applications like ureteral stents.